2013
DOI: 10.1556/jba.2.2013.012
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between alternate measures of maladaptive exercise, and their associations with disordered eating symptomatology

Abstract: Aims: The study sought to contribute to the measurement of maladaptive exercise by examining the psychometric properties of a variety of instruments and classification algorithms. The primary aim was to identify the items or scales necessary and sufficient to quantify the construct. A secondary aim was to comment on the construct validity of these measures by examining their relationships with disordered eating symptomatology. Methods: Questionnaire booklets comprising the Exercise Dependence Scale, the Obliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Therefore, this behaviour–reward association could lead to addiction to physical activity [ 5 , 60 ]. Furthermore, the scientific literature has consistently identified the thin ideal as a predictor of compulsive exercise pattern [ 61 ], as well as a reported significant correlation between concerns about weight gain and exercise addiction [ 29 ]. The data also demonstrated that the relationship between drive for thinness and exercise addiction was partially mediated by body image concerns (H 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this behaviour–reward association could lead to addiction to physical activity [ 5 , 60 ]. Furthermore, the scientific literature has consistently identified the thin ideal as a predictor of compulsive exercise pattern [ 61 ], as well as a reported significant correlation between concerns about weight gain and exercise addiction [ 29 ]. The data also demonstrated that the relationship between drive for thinness and exercise addiction was partially mediated by body image concerns (H 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown significant associations between drive for thinness with pathological exercise [ 28 ]. Indeed, drive for thinness indicates the tendency to desire (in an extreme way) to be thin and a fear of gaining weight, as well as attention and concerns about diet [ 26 , 27 ], and has consistently been found to be a significant predictor of exercise addiction in physical activities where weight loss is one of the primary goals [ 29 , 30 ]. Similarly, research has also focused on the effects of symptoms related to bulimia, defined by the presence of episodes in which large quantities of food are consumed in an uncontrolled way (bingeing), with consequent emotional agitation and psychological malaise [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it is possible that some of the participants belonging to the non-clinical subsamples included in the present analyses may qualify for a clinical diagnosis (Di Lodovico, Dubertret, & Ameller, 2018;Lease & Bond, 2013;Maraz, Urb an, Griffiths, & Demetrovics, 2015). On the other hand, the relationship of interest was examined within clinical samples in only six studies (Alexander, 2013;Bratland-Sanda et al, 2011;Formby, Watson, Hilyard, Martin, & Egan, 2014;Godier, 2015;Naylor, Mountford, & Brown, 2011;Sauchelli et al, 2016), of which four considered the CET for the assessment of MEB (Formby et al, 2014; Godier, 2015;Naylor et al, 2011;Sauchelli et al, 2016).…”
Section: Moderators Of the Relationship Between Meb And Edmentioning
confidence: 99%
“…Each subject's habitual physical activity was assessed based on a standardized questionnaire using FIT (frequency intensity time) index [30][31][32][33]. This index requires that points are allocated depending on the frequency, intensity and time spent performing physical activity per week.…”
Section: Assessment Of Habitual Physical Activitymentioning
confidence: 99%
“…The product of these three components (frequency, intensity and time) indicates the level of habitual physical activity. Thus, FIT index was calculated as follows: FIT index = (points for frequency)*(points for intensity)*(points for time) [30][31][32][33].…”
Section: Assessment Of Habitual Physical Activitymentioning
confidence: 99%